2002
DOI: 10.1021/cm010921o
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Lubrication:  Reaction of Phosphate Ester Vapors with Iron and Steel

Abstract: Aromatic phosphate esters such as triphenyl phosphate, tricresyl phosphate (TCP), and tri(tert-butylphenyl) phosphate, have been degraded in the presence of pure iron or metal alloys such as M-50 or 52100 steel. Among these volatile degradation products are those generated from the addition of an aromatic ring to the phosphate ester. Other products, which have been identified, include substituted biphenyls and diphenyl ethers derived from the decomposition of the above-mentioned addition product. Still other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…The only products that were observed were a few percent cresol and addition products from the addition of an aromatic ring to TCP. These products have been previously observed in this study on the reaction of iron with phosphate esters [23]. …”
Section: Samples Containing Tcpsupporting
confidence: 83%
“…The only products that were observed were a few percent cresol and addition products from the addition of an aromatic ring to TCP. These products have been previously observed in this study on the reaction of iron with phosphate esters [23]. …”
Section: Samples Containing Tcpsupporting
confidence: 83%
“…These studies also demonstrated the potential for vapor phase lubrication of TMC surfaces through small molecule adsorption. Due to the growing interest in materials and lubricants that can be incorporated into vapor phase lubrication schemes [10], the fruitful methodology developed in the ethanol study has been extended to the study additional adsorbates and is reported here.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown if phosphate ester additives will form a lubricious film on these surfaces. The nonheat-treated steels have been shown to react; however, heat-treated steals are currently under study [18]. The interaction of antioxidants, esters, and phosphate esters in the presence of various carbides has been shown to increase reactivity [19].…”
Section: Boundary Lubrication Additivesmentioning
confidence: 99%